PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI: Studi Kasus Pada Rumah Tahanan Negara Kelas IIA Yogyakarta - Hermawan, Beni Wahyu; Priyastiwi, Priyastiwi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to analyze the effect of leadership style, organizational culture, and motivation on employee performance at Class IIA Yogyakarta Detention Center and to analyze the influence of motivation in moderating the influence of leadership style and organizational culture on employee performance at Class IIA Yogyakarta Detention Center. This study uses a quantitative descriptive method with a causal research approach. The sample used in this study were employees of the Yogyakarta Class IIA State Detention Center, totaling 50 respondents with a data collection method, namely a questionnaire. Data analysis used a structural equation model or Structural Equation Modeling (SEM) by testing convergent validity, discriminant validity, construct reliability, and model validity to show that all the answers to the questions asked were significant with the SMARTPLS application tool version 4.0. The results of this study indicate that leadership style and organizational culture do not have a positive and significant effect on the performance of the Yogyakarta Class IIA State Detention Center employees, while motivation has a positive and significant influence on the performance of the Yogyakarta Class IIA State Detention staff. Furthermore, this study shows that motivation has no effect in moderating the effect of leadership style and organizational culture variables on the performance of Class IIA Yogyakarta State Detention Center employees.